Selank effects on morphine-induced analgesia in vivo experiments - A. V. Nadorova; I. V. Chernyakova; L. G. Kolik (LLC "Publisher OKI", 2022)
Background. The endogenous opioid system is involved in neuroadaptation produced by exogenous opioids. Synthesized on the basis of the regulatory peptide tuftsin, the anxiolytic selank inhibits the activity of enkephalin-degrading enzymes, increasing the level of leu-enkephalins in blood plasma.   The aim of the work was to evaluate the effect of selank (0,3 and 0,9 mg/kg, i. p.) on morphine-induced analgesia in animal models. Methods. The experiments were performed in inbred male mice C57Bl/6 (n = 77). The "hot plate" test was used to evaluate the analgesic effect during thermal stimulation of nociceptors when mice were placed on a metal plate heated to 55 ± 0,5 °C, followed by registration of the latent period of the reaction 30, 60, 90, and 120 minutes after the administration of morphine.   Results. Morphine at a dose of 3,0 mg/kg, i. p., caused antinociception with the maximum possible effect (MBE) of 9 %, selank at a dose of 0,9 mg/kg, without antinociception per se, when pretreated with the morphine, increased the latent reaction time, causing antinociception of 29,9 % MBE.   Conclusion. For the first time the data obtained on the synergistic effect of selank and morphine in attenuation of acute somatic pain.